Huaier aqueous extract induces apoptosis of human fibrosarcoma HT1080 cells through the mitochondrial pathway - CUI, YANG (Oncol Lett, 2015)
In recent years, aqueous extract of Trametes robiniophila Murr. (Huaier), a traditional Chinese medicine, has been frequently used in China for complementary cancer therapy. However, the mechanisms underlying its anticancer effects have yet to be elucidated. The present study aimed to evaluate the ability of Huaier extract to inhibit proliferation, promote apoptosis and suppress mobility in the fibrosarcoma HT1080 cell line in vitro. The cells were treated with gradient doses of Huaier extract at concentrations of 0, 4, 8 or 16 mg/ml for 24, 48 or 72 h. The cell viability and motility were measured in vitro using MTT, invasive, migration and scratch assays. The distribution of the cell cycle and the extent of cellular apoptosis were analyzed by flow cytometry. The apoptotic pathways were detected using a mitochondrial membrane potential transition assay and western blotting. The results revealed that the cellular viability decreased significantly with increasing concentrations of Huaier extract. In addition, cell invasiveness and migration were also suppressed significantly. It was demonstrated that Huaier extract induced G(2) cell-cycle arrest and cellular apoptosis in a time- and dose-dependent manner. The decreased mitochondrial membrane potential, the downregulation of B-cell lymphoma 2 and pro-caspase-3, and upregulation of Bcl-2-associated X protein, cleaved caspase-9 and caspase-3 suggested that Huaier extract induced the apoptosis of HT1080 cells through the mitochondrial pathway. The results of the present study indicate that Huaier extract is a potential complementary agent for the treatment of fibrosarcoma.